Urgensi Penginjilan Pribadi dalam Pelayanan Orang Muda - Dedi Agustino Harinei (STT Bala Keselamatan Palu, 2021)
Abstract: Youth ministry cannot be separated from the church that carries out Christ's mission in the world. But in general not all young Christians have a missionary spirit. The task of followers of Christ are to fellowship, teach, serve, witness, and go to make disciples of all nations of Christ. Personal evangelism is a noble task commanded by the Lord Jesus Christ. where there is a great work that God does to illuminate the darkness of the world. So that personal evangelism in youth ministry is something urgent and must be done immediately. From the results of the research, the authors found that young people in the ministry have not fully carried out their mission, considering that there are still many young Christians who do things that are not in accordance with Christian teachings. So that in ministry, young people must understand correctly about the urgency of personal evangelism as a command from the Creator to be carried out with full obedience by creation. Abstrak: Pelayanan orang muda adalah pelayanan yang tidak dapat dipisahkan dari gereja yang menjalankan misi Kristus didalam dunia. Namun pada umumnya tidak semua orang muda Kristen memiliki jiwa misi. Tugas pengikut Kristus adalah bersekutu, mengajar, melayani, bersaksi, dan pergi menjadikan semua bangsa murid Kristus. Penginjilan pribadi adalah tugas mulia yang di perintahkan oleh Tuhan Yesus Kristus. dimana ada karya agung yang Tuhan kerjakan untuk menerangi kegelapan dunia. Sehingga penginjilan pribadi dalam pelayanan orang muda adalah sesuatu yang urgen dan harus segera dikerjakan. Dari hasil penelitian, penulis mendapati bahwa orang muda yang ada dalam dunia pelayanan belum sepenuhnya menjalankan misinya, mengingat masih banyak orang muda Kristen yang melakukan hal-hal yang tidak sesuai dengan ajaran Kekristenan. Sehingga dalam pelayanan, orang muda harus memahami benar tentang urgensi penginjilan pribadi sebagai perintah dari Sang Pencipta untuk dilakukan dengan penuh ketaatan oleh ciptaan.